Salacia fruticosa methanol extract pretreatment attenuates scopolamine-induced cognitive decline and Alzheimer's disease-related pathology in zebrafish - Praveen Kumar Pasala; DSNBK Prasanth; Siva Prasad Panda; Vaishnavi Munnangi; Sharon Blessy; Sheikh F. Ahmad; Haneen A. Al-Mazroua (Asian Pacific Journal of Tropical Biomedicine)
Objective: To examine the effect of the methanolic extract of Salada fruticosa in a zebrafish model of scopolamine-induced Alzheimer’s disease. Methods: High-resolution liquid chromatography-mass spectrometry was used to characterize the phytochemical constituents of Salada fruticosa methanolic extract. The drug-likeness of these compounds was determined via the DruLiTo tool, and their acetylcholinesterase (AChE) binding affinities were studied by molecular docking. In in vivo studies, adult zebrafish were treated with 3.125, 6.25, and 12.5 mg/L of the extract for seven days and then immersed in scopolamine (100 μM/L) to induce cognitive deficits. T-maze and novel object recognition tests were used for behavioral studies. In addition, the activities of AChE, antioxidant enzymes, and myeloperoxidase were determined in brain tissue of zebrafish. Results: High-resolution liquid chromatography-mass spectrometry revealed that 40 phytoconstituents were present in the methanolic extract of Salacia fruticosa, and 27 compounds met Lipinski's rule of five, indicating good drug-likeness. Some compounds such as stylopine, p-coumaroylagmatine, and (-)-heliannuol E, demonstrated high AChE binding affinity. Moreover, pretreatment with the extract significantly mitigated zebrafish cognitive decline, as indicated by increased time spent at the novel object in novel object recognition test, as well as increased time spent and decreased latency in the green arm (P < 0.001). The extract also markedly lowered malondialdehyde and myeloperoxidase levels and AChE activity, and enhanced glutathione peroxidase and superoxide dismutase activities (P < 0.001) in zebrafish with scopolamine-induced Alzheimer’s disease. Histopathological studies revealed that Salacia fruticosa extract ameliorated scopolamine-induced abnormalities in neuronal cell morphology. Conclusions: Pretreatment with the methanolic extract of Salacia fruticosa reduces cognitive impairment, enhances antioxidants, and attenuates oxidative stress, highlighting its potential as a preventive agent for Alzheimer’s disease.